Evaluation of different bioimpedance methods for assessing body composition in Asian non-dialysis chronic kidney disease patients - Sean WY Lee; Clara Lee Ying Ngoh; Horng Ruey Chua; Sabrina Haroon; Weng Kin Wong; Evan JC Lee; Titus WL Lau; Sunil Sethi; Boon Wee Teo (Kidney Research and Clinical Practice, 2019)
Background : Chronic kidney disease (CKD) is associated with fluid retention, which increases total body water (TBW) and leads to changes in intracellular water (ICW) and extracellular water (ECW). This complicates accurate assessments of body composition. Analysis of bioelectrical impedance may improve the accuracy of evaluation in CKD patients and multiple machines and technologies are available. We compared body composition by bioimpedance spectroscopy (BIS) against multi-frequency bioimpedance analysis (BIA) in a multi-ethnic Asian population of stable, non-dialysis CKD patients.